Dispute settlement reports 1996 - World Trade Organization (Cambidge Cambridge University Press)
The disputes settlement reports of the World Trade Organisation include Panel and Appellate Body reports, as well as Arbitration, Awards,in disputes concerning the rights and obligations of WTO members under the provisions of the Marrakash Agreement Estab
v.1 pages 1 to 284
Keywords: International trade; Foreign trade regulation; Dispute regulation (Law)